2012
DOI: 10.1039/c2dt30695f
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect of ancillary ligands on the luminescence of bis[4,6-(di-fluorophenyl)-pyridinato-N,C2′]iridium(iii) complexes

Abstract: Two series of (dfppy)(2)Ir(L(N^O)) with different substituents were designed and successfully synthesized and the effect of substitution at the ancillary ligand on the photophysical and electrochemical properties of (dfppy)(2)Ir(L(N^O)) were investigated. The results indicate that the electron-donating group of -OMe at L(N^O) increases the PL quantum efficiencies of (dfppy)(2)Ir(L(N^O)) and the electron-withdrawing groups of -CF(3) and -F lower the PL quantum efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 58 publications
5
44
0
Order By: Relevance
“…The synthesis of compounds 1 [38] and 5a [29] was based on the method known from the literature. 1 H-and 13 C-NMR chemical shifts were calculated for both 19a,b and their enol forms ( Figure 1, Table 1) by GIAO method [30] using B3LYP functional [31][32][33] and the extended 6-311++G(2d,p) basis set [34].…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of compounds 1 [38] and 5a [29] was based on the method known from the literature. 1 H-and 13 C-NMR chemical shifts were calculated for both 19a,b and their enol forms ( Figure 1, Table 1) by GIAO method [30] using B3LYP functional [31][32][33] and the extended 6-311++G(2d,p) basis set [34].…”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al . also reported that electron with drawing groups lower the photoluminescence quantum efficiency in contrary to the electron donating group …”
Section: Photoluminescent Materialsmentioning
confidence: 99%
“…[41,50] Zhou et al also reported that electron with drawing groups lower the photoluminescence quantum efficiency in contrary to the electron donating group. [51,52] The cellular uptake ability of Ir (III) containing materials are mainly governed by their size, charge, hydrophilicity/hydrophobicity and the attached substituent group. The charge on the Ir (III) complexes affect their cellular uptake ability as the cationic complexes show better this activity than the anionic ones with much improved imaging efficacy.…”
Section: Iridium (Iii) Cyclometallates: As Bioimaging Agentsmentioning
confidence: 99%
“…Under the excitation of 532 nm (Xe lamp) Ir–COOH in this work has near‐infrared emission with maxima at 713 nm and 783 nm. According to the calculation method of photoluminescence quantum efficiency (Φ PL ), the Φ PL of Ir–COOH in deaerated DMF solution is 0.095 referring to fac ‐Irppy 3 (Φ PL =0.40, ppy=2‐phenylpyridine). [43] The phosphorescent lifetime at room temperature is 2.62 μs, which is very close to the formerly reported iridium(III) complex with similar main ligands …”
Section: Main Textmentioning
confidence: 99%